Effect of Heating Treatment on Synthetic Ceric Oxide as Inorganic Resin for Immobilization of Cadmium-(II) - S Soenarjo; C Wijaya; R Elzan; Sriyono Sriyono (PPIKSN-BATAN, 2005)
The immobilization of cadmium-(II) following nuclear reaction of 114Cd (n,γ) 115Cd → 115mIn or 112Cd (p,2n) 111In is absolutely needed concerning to the quality of resulting radioisotope products and the efficiency of enriched target utilization. This presented study is based on hypothesis that heating treatment on synthetic ceric oxide resin will increase the binding capacity of Cd(II) over the resin. The aim of the presented study is to gain more experimental data supporting utilization of synthetic ceric oxide resin as separating agent in production of indium radioisotopes using enriched cadmium targets. Experiments in cold system using natural cadmium, instead of high-enriched cadmium, have been carried out, wherein a method of UV-spectrophotometry was performed for quantitative determination of Cd(II). It was found that the synthesized ceric oxide dried at 90 - 100°C was in form of hydrate compound formulated as CeO2.q H2O where q = (0.8868 ± 0.0026). The value of q descended to 0.1706 and to 0.0400 as influenced by heating treatment up to 400°C and 800°C respectively along with a change on the crystallinity of the ceric oxide from semi crystalline to purely crystalline. The binding capacity of Cd(II) on ceric oxide dried at 90 – 100°C was found to be (4.71 ± 0.08) × 10-2 mg Cd(II)/mg resin and significantly increased to (11.71 ± 0.24) × 10-2 and to (14.70 ± 0.17) × 10-2 mg Cd(II)/mg resin due to heating treatment up to 400°C and 800°C respectively. It can be concluded that the synthetic ceric oxide resin enable to be exploited for immobilization of Cd(II).